The Potency of Aluminum Hydroxide Nanoparticles for Dengue Subunit Vaccine Adjuvant - SABAR PAMBUDI; ETIK MARDLIYATI; SILMI RAHMANI; DAMAI RIA SETYAWATI; TIKA WIDAYANTI; ANGELINA GILL; ASRI SULFIANTI; WHINIE LESTARI (Microbiology Indonesia, 2018)
The potency of aluminum hydroxide as an adjuvant in vaccine development is considered to depend on its particle size. In previous studies, we have successfully prepared two size particle, micro, and nano, aluminum hydroxide gel (alum) adjuvants. The potency of those particles as a candidate of adjuvant is needed to be characterized. In this study, we formulated our adjuvants with purified DENV3 pre Membrane Envelope (prM-E) recombinant protein and evaluated the induction of nitric oxide level in mouse macrophage RAW 264.7 cells. We prepared the alum adjuvant by precipitation-homogenization methods with an agitation rate at 11,000xg. Secreted prM-E recombinant protein was collected from Pichia pastoris X-33 fermentation which produced using bioreactor. Recombinant protein purification was carried out by anion exchange chromatography followed with size exclusion chromatography. The purified prM-E recombinant protein was observed as a single band around 70 -1k Da with a concentration of 105 mg mL . Complex nanoparticles alum with prM-E protein significantly (p<0.05) induced the nitric oxide level. Further analysis should be conducted in order to discover the detail molecular mechanism of nanoparticle alum adjuvant, recombinant protein, and cellular immune response.